Punctum on two different transcription factors regulated by PGC-1α: Nuclear factor erythroid-derived 2-like 2 and nuclear respiratory factor 2 - Baldelli, Sara; Aquilano, Katia; Ciriolo, Maria R. (Biochimica et biophysica acta, 2013)
The transcription factor nuclear factor-erythroid-derived 2-like 2 (official symbol: NFE2L2, alias: Nrf2) is a master regulator of antioxidant defense system, which makes it an attractive target for manipulations that aim to increase cellular resistance to oxidative stress. Nuclear respiratory factor 2 or GA binding protein transcription factor alpha (official symbol: GABPA, alias: NRF2) functions as a transcription factor that activates the expression of some key metabolic genes regulating cellular growth and nuclear genes required for mitochondrial respiration as well as mitochondrial DNA transcription and replication. Despite the evident structural and functional differences, confusion has occurred in bibliographic databases due to the shared symbol NRF2 for these transcription factors. Such confusion has worsened after the discovery that the transcriptional co-activator peroxisome proliferator activated receptor gamma co-activator 1 alpha (PGC-1α) could control the signaling pathway of both NFE2L2 and GABPA through distinct molecular mechanisms. This review will summarize the implications of NFE2L2 and GABPA in various human patho-physiological conditions and how PGC-1α can regulate their different signaling axis. This review underlines the overlapping functions between PGC-1α, NFE2L2 and GABPA, which alteration could induce the development of human pathological states. The comprehension of molecular mechanisms that modulate the intersection between these proteins will be important to identify new signaling axis involved in lifespan extension as well as novel targets for therapeutic interventions. •PGC-1alpha co-activates NFE2L2 and GABPA.•NFE2L2 is a master regulator of antioxidant/detoxifying system.•GABPA controls the transcription of many mitochondrial/metabolic genes.•NFE2L2, GABPA and PGC-1alpha are implicated in the same patho-physiological processes.